Pharmaceutical chemistry - Barber, Jill; Rostron, Chris (Oxford : Oxford University Press, 2013)
This volume provides a wide-ranging overview of organic chemistry as applied to the study and practice of pharmacy. Drugs are simply chemicals, so to fully understand their manufacture, formulation, and the way they work in our bodies, an understanding of organic compounds and their reactions is essential --
pharmacy bookfair2016
Keywords: Pharmaceutical chemistry